Programming Languages and Systems 9th Asian Symposium, APLAS 2011, Kenting, Taiwan, December 5-7, 2011. Proceedings - Yang, Hongseok; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 9th Asian Symposium on Programming Languages and Systems, APLAS 2011, held in Kenting, Taiwan, in December 2011. The 22 revised full papers presented together with 4 invited talks and one system and tool presentations were carefully reviewed and selected from 64 submissions. The papers are organized in topical sections on program analysis; functional programming; compiler; concurrency; semantics; as well as certification and logic.
Keywords: Computer science; Software engineering; Data protection; Logic design; Computer Science; Programming Languages, Compilers, Interpreters; Software Engineering; Logics and Meanings of Programs; Systems and Data Security; Programming Techniques; Mathematical Logic and Formal Languages